1988
DOI: 10.1111/j.1440-1746.1988.tb00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactose malabsorption in Central Australian Aboriginal children hospitalized with acute enteritis

Abstract: The prevalence and duration of lactose malabsorption was studied in 64 Central Australian Aboriginal children requiring hospitalization for acute enteritis. Lactose malabsorption was determined by the breath-hydrogen test. Sixty-nine per cent were shown to malabsorb lactose, a figure similar to that for well nourished urban European children, hospitalized for acute enteritis. Whereas 90 per cent of the European children became lactose-tolerant 1 month later, only three of 32 aboriginal children were lactose-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Human enteric CoV causes moderate to severe villous atrophy in animal models, with virus particles visible in enterocytes of the large and small intestine ( 36 , 37 ). CoV-like particles have also been found in degenerating jejunal epithelial cells of adults in India with histological evidence of malabsorption due to environmental enteric dysfunction and among Aboriginal children with lactose malabsorption post-gastroenteritis ( 38 , 39 ). However, the exact mechanisms of COVID-19–induced gastrointestinal symptoms of nausea, vomiting, and loss of taste remain elusive ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Human enteric CoV causes moderate to severe villous atrophy in animal models, with virus particles visible in enterocytes of the large and small intestine ( 36 , 37 ). CoV-like particles have also been found in degenerating jejunal epithelial cells of adults in India with histological evidence of malabsorption due to environmental enteric dysfunction and among Aboriginal children with lactose malabsorption post-gastroenteritis ( 38 , 39 ). However, the exact mechanisms of COVID-19–induced gastrointestinal symptoms of nausea, vomiting, and loss of taste remain elusive ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Human enteric coronavirus causes moderate to severe villous atrophy in animal models with virus particles visible in enterocytes of large and small intestine 45,46 . Coronavirus-like particles have also been found in degenerating jejunal epithelial cells of adults in India with histological evidence of malabsorption due to environmental enteric dysfunction and among Aboriginal children with lactose malabsorption post gastroenteritis 47,48 . However, the exact mechanisms of COVID-19 induced gastrointestinal symptoms of nausea, vomiting and loss of taste remain elusive 49 .…”
Section: Protein Energy Malnutritionmentioning
confidence: 99%
“…Aboriginal children from remote communities in northern Australia have high rates of hospital admission for diarrhoea and failure to thrive 1 . Diarrhoeal disease in Aboriginal children is frequently complicated by lactose intolerance, 2 leading to osmotic diarrhoea, acidosis, hypokalaemia and severe dehydration, requiring urgent air evacuation to hospital in Darwin. In a previous study, we showed that these complications are related to the severity of small bowel mucosal damage and that apparently healthy Aboriginal children have an underlying tropical/environmental enteropathy 3 .…”
Section: The Three Low‐lactose Milk Formulas Used In the Trialmentioning
confidence: 99%
“…Two ran­domized trials in the 1970s in Aboriginal children admitted with diarrhoea and/or malnutrition showed significantly greater weight gain on low‐lactose milk compared to normal milk 6,7 . In addition, a breath hydrogen study found that 90% of Aboriginal children under 2 years of age were still lactose intolerant 3 months after admission with acute gastroenteritis, compared to only 10% of non‐Aboriginal subjects 2 …”
Section: The Three Low‐lactose Milk Formulas Used In the Trialmentioning
confidence: 99%